Pathogenesis of acute pancreatitis (2008)
In the pathogenesis of acute pancreatitis, independent of the etiology, the activation of pancreatic enzymes inside the pancreatic acine is an early event. This causes initial injury to acinar pancreatic cells. The level of pancreatic injury determines the severity of the disease. It also determines whether or local and/or systemic endothelial inflammation reactions are triggered. These reactions can cause complications and are important for the prognosis of this medical condition. © Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.